Klasifikasi Penyimpangan Tumbuh Kembang Anak Menggunakan Algoritme C5.0 - Dyah Ayu Wahyuning Dewi; Imam Cholissodin; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Developmental deviation of the child's development is a disruption of the process of growth and development resulting in the child experiencing a phase that is inhibited compared to other normal children. If it is not immediately treated, it is feared that the developmental deviation of the child's growth will be increasingly difficult to handle. For that we need the awareness of parents to immediately check the condition of the child at the doctor, in order to alleviate these irregularities. However, the number of patients is not proportional to the number of doctors available. Lack of doctors can result in slow handling of patients. To deal with this, a system of diversification of child growth and development was made using the C5.0 algorithm. In this study will be classified into three types of developmental deviations of children, namely autism, down syndrome, and ADHD (Attention Deficit Hyperactivity Disorder). C5.0 algorithm is one of the decision tree algorithms and is a development of C4.5. The difference in C4.5 and C5.0 is that in the C5.0 algorithm there is a boosting process, so that it can provide better accuracy than the C4.5 algorithm. From the research that has been done, the average value of accuracy in testing the amount of training data is 95.9%, the average accuracy in testing the number of trials is 97.3%, and the comparison testing of C4.5 and C5.0 results in accuracy at C5.0 is 93.33% while the accuracy at C4.5 is 87.61%. The things that affect the accuracy value are the large amount of data, and the number of trials used.